Analysis of light weight fractions of coal-based crude oil by gas chromatography combined with mass spectroscopy and flame ionization detection. (1st April 2019) - Li, Wen-ying; Wang, Wei; Mu, Hai; Li, Wang; Ye, Cui-ping; Feng, Jie
Graphical abstract: Highlights: An approach to calculate the effective carbon number is suggested. A FID response factor prediction formula is deduced and verified. How to judge the effectiveness of relative response factors of FID is proposed. Material balance is obtained by quantitative analysis of coal-based crude oil. Abstract: To realize the fast and accurate determination of coal-based crude oils, gas chromatography combined with mass spectrometry and flame ionization detection is employed to assist in qualitative and quantitative analysis. In addition, material balance is introduced into the analysis at the same time as a constraint. A new equation is deduced and verified, which can predict flame ionization detection relative response factors mainly by the molecular formula of the compounds. Meanwhile, the formula is integrated with the area normalization method. The standard compound addition method is employed to test the reliability as well, and the recovery experiments show that the designed system is simple, fast, accurate and effective. Finally, the analytical method system is applied to characterize the light weight fractions of coal-based crude oil, and the results show that approximately 70–80 wt% of the components can be balanced.